Assessment of the recruitment process of NRB Bank Bangladesh Ltd. - Chakrabortty, Shaswaty (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2018.